THE EFFECT OF PERCEPTION OF EASE, PRICE, AND PROMOTION ATTRACTION ON INTEREST IN USING OVO APPLICATIONS - Ernie Mardiany Djaenudin (Jurnal Pendidikan Nusantara, 2022)
This study was conducted to determine the effect of perceived convenience, price, and promotional attractiveness on interest in using the OVO application. The study was conducted in Supermal Karawaci with 100 respondents using non-probability sampling purposive sampling technique with research respondents being new users, active users, and occasional users. The instrument test was conducted by testing the validity using the product-moment method. The analytical technique used was multiple regression analysis. Based on the results of the study, partially the effect of the perceived convenience variable has a significant positive impact on interest in the use, the price variable has positive and significant effects on appeal in use, and the promotional attractiveness variable has a positive and significant impact on interest in service. Simultaneously the variables of Perception of Ease, Price, Promotional Attractiveness have a positive and significant effect on Interest in Use.